NALISIS KOINTEGRASI INDEKS HARGA SAHAM DI 5 (LIMA) NEGARA TERHADAP INDEKS HARGA SAHAM GABUNGAN DI INDONESIA (STUDI KASUS PADA NEGARA CHINA, JEPANG, KOREA, TAIWAN, DAN SINGAPURA) - Riesa Desvita Sari; Andrieta Shintia Dewi (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2018)
The economic crisis that struck China caused People Bank of China (PBOC) to establish devaluation strategy to Yuan on 11th of August 2015. This Strategy directly affects the shift on stock price index in the Chinese stock exchange and several global stock exchange. The global stock exhange willingly or not are forced to encounter the same condition, this caused by the volatility and incidents on a stock exchange in a country may be associated with the stock exchange of other countries. The purpose of this study is to analyze the long-term relationship (cointegration) between stock price index in 5 (five) countries on Indonesia Composire Index in Indonesia. The stock price index used in this study is Indeks Harga Saham Gabungan (Indonesia, SSE Composite Index (China), Nikkei 225 (Japan), KOSPI Composite Index (Korea), TSEC Weighted Index (Taiwan), and STI Index (Singapore). This study used the quantitative approach. The data used time series data, that started from August 1, 2012 until August 31, 2015. The cointegration was tested using the Johansen method, which was done in two stage. The first stage using the multivariate cointergration test, by performing overall index of IHSG, SSEC, N225, KOSPI, TWII, dan STI. The second stage using the bivariate cointegration test, which was done by pairing the stock price index. Based on the results aqcuired from the data, it can be concluded that there is long-term relationship (cointegration) between stock price index by overall and in pairs. The KOSPI-IHSG index pair is the mostsignificant long-term index of stock price index, so it can be said that KOSPI index is the index that most influence IHSG.